Angiogenic inhibitors in gastric cancers and gastroesophageal junction carcinomas: A critical insight. Issue 2 (August 2015) - Aprile, Giuseppe; Ongaro, Elena; Del Re, Marzia; Lutrino, Stefania Eufemia; Bonotto, Marta; Ferrari, Laura; Rihawi, Karim; Cardellino, Giovanni Gerardo; Pella, Nicoletta; Danesi, Romano; Fasola, Gianpiero
Highlights We discuss the rationale for the development of antiangiogenics in gastric cancers. We review the results of key phase 2 and phase 3 clinical trials. We present the state-of-the-art of current research in the field. We reason on possible future scenarios of antiangiogenic treatments.